Kargil, the crisis and its implications. - Nehru Memorial Museum and Library (New Delhi Nehru Memorial Museum and Library, 1999)
Deliberations of a debate.
Keywords: Kargil (India) -- History, Military -- Congresses; India -- Military relations -- Pakistan -- Congresses; Pakistan -- Military relations -- India -- Congresses